HPTLC Fingerprinting Profile of Root of Punarnava (Boerhaavia diffusa Linn.) - Raj, Divya; Ansary, P Y; Ommen, Sara Moncy; Shincymol, V V (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: The root of Punarnava (Boerhaavia diffusa Linn.) possesses high therapeutic value and is used in many conditions such as Gulma (abdominal tumor), Pandu (anemia), Yakrit roga (liver disorders), Pleeha roga (splenic disorders), and Hridroga (cardiac disorders). But, before internal administration, it is essential to confirm the drug’s authenticity and quality. Obtaining authentic chromatographic fingerprints that accurately reflect the pharmacologically active and chemically distinctive components of the drugs is essential. High-performance thin-layer chromatography (HPTLC) fingerprinting helps to know the authenticity and identity of the drug. It is highly useful to avoid the unnecessary usage of adulterated drugs. Detection of the marker compound is essential to know the mechanism of action a drug in particular diseases and systems of the body. Materials and Methods: In the present study, methanolic extract of root powder of B. diffusa Linn. was selected. Solvent system used was toluene, ethyl acetate, and formic acid (5:4:0.5). After development, the plate was examined under ultraviolet light 254 nm, 366 nm, and after derivatization in white light. Results and Discussion: While analyzing the HPTLC fingerprinting profile of Punarnava (B. diffusa Linn.), at 254 nm, it showed six peaks and at 366 nm, it showed ten peaks. At 254 nm, highest peak was obtained at Rf 0.03 with a total area of 4390.5 (AU). At 366 nm, highest peak obtained at Rf 0.02 with a total area of 7211.2 (AU). Conclusion: For identification of medicinal plants, the HPTLC fingerprinting profile is a crucial component of the standardization of herbal drugs. At 254 nm, it shows 6 peaks and at 366 nm, it shows 10 peaks.